THE EFFECT OF ESG DISCLOSURE, LIQUIDITY, AND PROFITABILITY ON FIRM VALUE: THE MODERATING ROLE OF DIVIDEND POLICY - Najma Kamilah Rizkianti; Lena Erdawati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study investigated the effect of Environmental, Social, and Governance (ESG) Disclosure, Liquidity, and Profitability on Firm Value, with dividend policy as a moderating variable, in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative associative approach was employed, and the sample was selected using purposive sampling, yielding 29 firms and 145 panel data observations. Data analysis was conducted using moderated regression analysis with EViews 13, and the fixed effect model was identified as the best-fitting model. The findings revealed that environmental, social, and governance disclosure and liquidity did not significantly influence firm value, whereas profitability demonstrated a positive and significant effect. Furthermore, dividend policy failed to moderate the relationships between environmental, social, and governance disclosure, liquidity, and profitability with firm value, indicating that dividend policy did not function as a moderating variable in this context. These results highlighted the limited role of environmental, social, and governance disclosure and liquidity in enhancing firm value within the food and beverage sector, while profitability remained a key determinant. The absence of moderation by dividend policy suggested that firm value in this industry was more directly shaped by operational performance rather than dividend distribution strategies. This study contributed empirical evidence from an emerging market perspective and offered practical implications for corporate managers and investors in formulating value-enhancing strategies.